A Comparison on Behavioral Patterns of Engagement Between Two Different Classroom Settings: With and Without Student Response Systems (SRS) - Nadarajan, Pooveneswaran; Muhamad, Maizatulliza (Asian Journal of Assessment in Teaching and Learning, 2021)
This study investigated the impact of student response system (SRS) on students’ engagement in English language proficiency classrooms. It compared patterns of engagement exhibited by students’ physical behaviours during language classroom activities in two different settings – with and without the use of SRS. This qualitative study gathered data through classroom observations using field notes and observational checklist. All the data were analysed qualitatively using thematic analysis approach. Altogether, three lessons utilizing SRS and three lesson without the utilization of SRS were observed and analysed. The findings showed that students’ behaviours during lessons with SRS indicated positive engagement in the classrooms unlike their behaviours during lessons without SRS. The results of this study implied that SRS could be a preferred choice of interactive, educational tools that could help educators to engage their students during the process of language teaching and learning.